The antimicrobial possibilities of green tea - Reygaert, Wanda C. (Frontiers in Microbiology, 2014)
Green tea is a popular drink, especially in Asian countries, although its popularity continues to spread across the globe. The health benefits of green tea, derived from the leaves of the Camellia sinensis plant, have been studied for many years. Fairly recently, researchers have begun to look at the possibility of using green tea in antimicrobial therapy, and the potential prevention of infections. The particular properties of catechins found in the tea have shown promise for having antimicrobial effects. There are four main catechins (polyphenols) found in green tea: (-)-epicatechin (EC), (-)-epicatechin-3-gallate (ECG), (-)-epigallocatechin (EGC), and (-)-epigallocatechin-3-gallate (EGCG). Three of these, ECG, EGC, and EGCG have been shown to have antimicrobial effects against a variety of organisms. These catechins have exhibited a variety of antimicrobial mechanisms. The results of studies on the antimicrobial effects of green tea have shown that the potential for preventive and therapeutic purposes is present. Further data collection on studies performed with human consumption during the course of infections, and studies on the occurrence of infections in populations that consume regular amounts of green tea will be necessary to complete the picture of its antimicrobial possibilities.